Co/Cr co-doped MgGa2O4 nanoparticles: Microstructure and optical properties. (January 2016) - Duan, Xiulan; Liu, Jian; Yu, Fapeng; Wang, Xinqiang
Graphical abstract: The Ga 2p3/2 spectra consist of two peaks, corresponding to Ga 3+ ions placed at octahedral and tetrahedral sites, respectively. The fraction of tetrahedral Ga 3+ ions (∼1117 eV) increases with increasing doping concentration. Highlights: Structural and properties of Co 2+ /Cr 3+ : MgGa2 O4 nanoparticles were characterized. The distribution of cations was studied using XPS. The inversion degree increased with increasing content of doping ions. The doping concentration has also effect on absorption and emission properties. Optical properties of nanoparticles were discussed based on the structural results. Abstract: MgGa2 O4 nanoparticles co-doped with Co 2+ /Cr 3+ ions were prepared by a citrate sol–gel method. Their microstructure and optical properties were studied using X-ray powder diffraction (XRD), infrared spectroscopy, X-ray photoelectron spectroscopy (XPS), absorption and fluorescence spectroscopy. MgGa2 O4 nanoparticles with the size of 10–30 nm were obtained when the precursor was annealed at 800 °C. Results indicated that Ga 3+ and Mg 2+ cations occupied the octahedral sites as well as the tetrahedral sites in samples. The inversion degree of Ga or Mg increased with increasing content of doping ions. Absorption spectra indicated that Co 2+ and Cr 3+ ions entered both the tetrahedral and octahedral sites of spinel structure by substituting Mg 2+ and Ga 3+ ions, respectively. Emission spectra of the co-doped MgGa2 O4 showed a broad emission band peaking at 700 and 680 nm, relevant to the emission characteristic of octahedral Cr 3+ and tetrahedral Co 2+ ions.